EXAMINATION OF ECONOMICS ATTITUDES AND ONLINE LEARNING READINESS ON LEARNING OUTCOMES - Fitrayati, Dhiah; Wahyono, Hari; Mukhlis, Imam; Andayani, Endang Sri (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
The study aims to determine the effect of attitudes towards economics and online learning readiness on mediating the effect of attitudes towards economics on learning outcomes. The research population was active students of the Faculty of Economics and Business, Surabaya State University, in 2022/2023, with a sample size of 353 students. Quantitative research using structural equation model analysis. The results showed that attitudes towards economics and learning readiness significantly positively affected learning outcomes. In addition, online learning readiness partially can mediate attitudes towards economics on learning outcomes.